Over-Expression of Centromere Protein U Participates in the Malignant Neoplastic Progression of Breast Cancer - Hao, Xiaomeng; Qiu, Yufan; Cao, Lixia; Yang, Xiaonan; Zhou, Dongdong; Liu, Jingjing; Shi, Zhendong; Zhao, Shaorong; Zhang, Jin (Frontiers in Oncology, 2021)
The expression of Centromere Protein U (CENP-U) is closely related to tumor malignancy. Till now, the role of CENP-U in the malignant progression of breast cancer remains unclear. In this study, we found that CENP-U protein was highly expressed in the primary invasive breast cancer tissues compared to the paired adjacent histologically normal tissues and ductal carcinoma in situ (DCIS) tissues. After CENP-U was knocked down, the proliferation and colony-forming abilities of breast cancer cells were significantly suppressed, whereas the portion of apoptotic cells was increased. Meanwhile, the PI3K/AKT/NF-κB pathway was significantly inhibited. In vivo studies showed that, the inhibition of CENP-U repressed the tumor growth in orthotopic breast cancer models. Therefore, our study demonstrated that the CENP-U might act as an oncogene and promote breast cancer progression via activation of the PI3K/AKT/NF-κB pathway, which suggests a promising direction for targeting therapy in breast cancer.